Pergeseran Fungsi Aplikasi Tinder dan Dampaknya terhadap Perilaku Pergaulan Bebas di Kalangan Anak Muda Indonesia: Penelitian - Sabrina, Ghea Rae (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Tinder, an online dating application, was initially designed to help users find new friends or long-term partners. However, its function has shifted significantly among Indonesian youth. This study aims to describe the misuse of Tinder, identify the factors contributing to this shift, and analyze its impact on promiscuous behavior. Using a qualitative phenomenological approach, the research collected data through in-depth interviews with Tinder users aged 20–35, observations of application usage, and relevant literature review. The findings reveal that Tinder is no longer used solely for romantic relationship building but has increasingly become a platform for non-committal interactions such as friends with benefits (FWB), one-night stands (ONS), and other forms of sexual engagement. This functional shift is influenced by open-minded attitudes, strong curiosity, and environmental support. Consequently, the misuse of Tinder contributes to the rise of promiscuous behavior among Indonesian youth. The study highlights the need for improved digital literacy and responsible supervision in the use of online dating applications.